2020
DOI: 10.1038/s41598-020-70678-8
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline/Ag nanoparticles/graphene oxide nanocomposite fluorescent sensor for recognition of chromium (VI) ions

Abstract: Selective determination of toxic hexavalent chromium (Cr(VI)) is a stringent important due to its huge negative impact on the health and environment. Recently, the high sensitivity, rapidness, and cost-effectiveness of the fluorescent sensors for Cr(VI) have been developed. A fluorescent nanocomposite (NC) has been synthesized based on doped polyaniline (PANI), 2-acrylamido-2-methylpropanesulfonic acid (AMPSA) capped Ag nanoparticles (NPs) and graphene oxide (GO) quantum dots (QDs) via in situ reaction for hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 41 publications
2
49
0
Order By: Relevance
“…In addition, it is observed that the peak at 2550 cm –1 related to the reaction of the S–H group of excess MPA with N-GQDs disappears. 31 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, it is observed that the peak at 2550 cm –1 related to the reaction of the S–H group of excess MPA with N-GQDs disappears. 31 …”
Section: Resultsmentioning
confidence: 99%
“…This confirms the formation of nanocrystals of N-GQDs. 31 , 38 40 In addition, the HRTEM images of the prepared CIS/ZnS QDs are highly crystalline and the size of the nanocrystals is estimated to be in the range of 3.18–4.57 nm. The interplanar spacing is 0.33 nm for the (112) plane.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Engineered nanoparticles are defined as a material has a particle size ranged from 1 to 100 nm 1 . Nanoscience recently plays an important role by providing new materials with unique characteristics for remediation/treatment and sensing applications 2 6 . The research field called “nanoecotoxicology” explores the impacts of nanoparticles on the organisms and their ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Polyaniline (PANI) and its nanocomposites (NCs) with high stability, high electroactivity, high conductivity and low cost are candidate to apply in the fields of sensors 6 , 26 29 , energy storage 10 and water treatment 5 , 30 – 32 . Yslas et al reported that there is no toxicological effect of PANI nanofibers for Rhinella arenarum larvae exposed to PANI even at the highest concentration, 400 mg/L 33 .…”
Section: Introductionmentioning
confidence: 99%